Deusas que dançam: análises sobre as subjetividades e relações de poder de professoras de Danças Pélvicas - MAYARA CRISTINA DOS SANTOS VIEIRA (2024)
They knew they could be arrested. The general objective of this research was to investigate the processes of subjectivities and power relations in the constitution of women teachers of Pelvic Dances. The specific objective focuses on problematizing tensions and displacements through the complexities and potentialities observed during the route construction. This research involved qualitative methodology, in which the data collected were produced using two research instruments, one questionnaire and a semi-structured interview, both online, with the participation of nine Pelvic Dance teachers. The investigation also went through the bricolage methodology, using the goddesses as analytical tools mythological, Foucauldian discourse analyses, moving through intersectionality in a constructionist approach and decoloniality, articulating with the markers social difference. Teachers who had family support regarding their decisions in their trajectories in Pelvic Dances, demonstrated that this factor was a facilitator for delve deeper into dance studies and, in some cases, their emotional relationships They ended up becoming his work partners. Religion was also a point of highlighted in the analyses, as it was controversial within the life process of interviewed, not only Christianity, but mainly it, due to the influence as a colonized country. Other factors also contributed to these relationships of power and subjectivities were produced, such as: gender, race, class, sexuality, profession, precarious work, machismo, prejudice, harassment, schooling, income, bodies, age, privilege, prostitution, sensuality, sorority, media and technologies. The research results offered dialogues and reflections on the universe of Pelvic Dances, revealing that it goes beyond an artistic expression, highlighting its role in the cultural scene and its relevance in contemporary society.